Carotid Intima-Media Thickness Is Increased In Patients With Treated Mucopolysaccharidoses Types I and II, And Correlates With Arterial Stiffness - Wang, Raymond Y. (2013)
BACKGROUND: Treatments for mucopolysaccharidoses (MPS) have increased longevity, but coronary artery disease (CAD) and cardiovascular complications cause mortality in a high percentage of patients. Non-invasive measures of sub-clinical atherosclerosis, such as carotid intima-media thickness (cIMT) and arterial stiffness, may be useful for prediction of CAD outcomes in MPS patients. OBJECTIVES: To determine if cIMT and arterial stiffness are abnormal in MPS I and II patients compared to healthy controls. METHODS: MPS patients underwent carotid artery ultrasonography, and electronic wall-tracking software was used to measure cIMT, carotid artery compliance (cCSC), distensibility (cCSD), and incremental elastic modulus (cIEM). Control data from healthy subjects were obtained from a different study that utilized identical testing within the same laboratory. RESULTS: A total of 406 healthy controls and 25 MPS patients (16 MPS I, 9 MPS II) were studied. All MPS patients had or were receiving treatment: 15 patients (6 MPS I, 9 MPS II) were receiving enzyme replacement therapy (ERT), 9 patients (all MPS I) had received hematopoietic stem cell transplant (HSCT), and 1 patient with MPS I had received HSCT and was receiving enzyme replacement therapy (ERT). MPS patients had significantly higher mean (±SD) cIMT (0.56 ± 0.05 mm) compared to controls (0.44 ± 0.04 mm; adjusted p < 0.001). MPS patients also had increased stiffness compared to controls, showing significantly lower cCSC (0.14 ± 0.09 mm(2)/mmHg versus 0.16 ± 0.05 mm(2)/mmHg; adjusted p = 0.019), and higher cIEM (1362 ± 877 mmHg versus 942 ± 396 mmHg; adjusted p < 0.001). cCSD in MPS patients was lower than control (29.7 ± 16.4% versus 32.0 ± 8.2%) but was not statistically; p = 0.12. Among MPS patients, cCSD showed a significant association with cIMT (p = 0.047), while the association between cIEM and cIMT approached significance (p = 0.077). No significant differences were observed in cIMT, cCSD, cCSC, and cIEM between MPS I and MPS II patients. CONCLUSIONS: Despite treatment, MPS patients had higher cIMT compared to healthy controls, indicating this marker of sub-clinical atherosclerosis may be a useful predictor of CAD outcomes. The association of arterial stiffness measures with cIMT suggests that mechanical and structural changes may occur in concert among MPS patients. Although yet to be confirmed, increased cIMT and arterial stiffness in MPS I and II patients may be a consequence of inflammatory signaling pathways triggered by heparan or dermatan sulfate-derived oligosaccharides. Prospective, longitudinal studies will need to be performed in order to evaluate the usefulness of these carotid measurements as predictors of adverse CAD outcomes in MPS patients.